Fundamentals of Operative Dentistry, Third Edition - Konstantinos X. Michalakis, DDS, PhD (Journal of Prosthodontics, 2006)
This clinical report documents the treatment of a 63-year-old Caucasian female Prosthodontic Diagnostic Index Class III patient using dental implants and a fixed prosthetic reconstruction